Giant cell tumour of the flexor tendon sheath of the hand - Mallik, M. R.; Nayak, S. S.; Maharaj, R. C.; Mishra, N. R.; Chand, D. K.; Chaterjee, A. (International Journal of Research in Orthopaedics, 2019)
Background: Giant cell tumor of tendon sheath is a benign soft tissue lesion most commonly found in the flexor aspect of hand and wrist. Recurrence of the tumor is common even after excision. Methods: It is an observational study where we present a review of 10 cases for which excision was done and were kept for regular follow up for minimum 6 months. Results: No recurrences noted in our series with minimum six months to maximum two years follow-up though review literature shows 10-40% recurrence rates. Conclusions: Complete excision with regular follow up care is indicated for this neoplasm due to its high propensity towards recurrence. The most important factor deciding recurrence pattern is incomplete excision and leaving behind satellite nodules.